PENERAPAN PRINSIP SYARIAH DALAM PERMODALAN BANK SYARIAH - Wahyu Muhammad, Danang (Jurnal Media Hukum, 2014)
Islamic BankÂ  is a bankÂ  thatÂ  is based on Syariah principles. The principles mustÂ  always be obeyed bothÂ  inÂ  the establishment andÂ  in the operational,Â  includingÂ  theÂ  financial capital.Â  RegardingÂ  the capital,Â  it must not come fromÂ  aÂ  sourceÂ  thatÂ  isÂ  consideredÂ  asÂ  haramÂ  accordingÂ  toÂ  SyariahÂ  principles, which willÂ  causeÂ  a mixÂ  between halalÂ  andÂ  haram.Â  SomethingÂ  thatÂ  isÂ  halal mustÂ  beÂ  strictlyÂ  separatedÂ  fromÂ  somethingÂ  thatÂ  isÂ  haram,Â  andÂ  vice versa. This paper discusses The Application of Syariah Principles in Islamic Bank Capitalization. Several principles areÂ  appliedÂ  and mustÂ  beÂ  obeyed byÂ  IslamicÂ  Bank,Â  namely: Al-TaâawanÂ  Principle,Â  PrincipleÂ  of AvoidingÂ  (Al-Ikhtinaz)Â  fromÂ  gharar, masyir,Â  andÂ  riba.Â  AsÂ  aÂ  partÂ  of IslamicÂ  Economy,Â  theÂ  activitiesÂ  ofÂ  IslamicÂ  BankÂ  canÂ  be observedÂ  fromÂ  fourÂ  pointsÂ  ofÂ  view,Â  namely;Â  ilahiyahÂ  economy,Â  ahlaqÂ  economy, humanityÂ  economy,Â  and balance economy. Meanwhile, from several viewsnof Muslim Economists,Â  it can be concluded that the core of IslamicÂ  teachingÂ  isÂ  tauhid, which meansÂ  thatÂ  allÂ  humanÂ  activitiesÂ  inÂ  the world,Â  including economy,Â  is merely forÂ  ibadahÂ  âÂ  actÂ  ofÂ  devotionÂ  â whichÂ  isÂ  aimedÂ  atÂ  followingÂ  oneÂ  law,Â  AllahâsÂ  law.Â  TheÂ  valueÂ  ofÂ  tauhid,Â  in practice,Â  isÂ  interpretedÂ  in manyÂ  valaesÂ  andÂ  thereÂ  areÂ  three basicÂ  valuesÂ  thatÂ  become distinguishing factors betweenÂ  Islamic economy and other, namely adl, khilafah, and takaful.Â  It can be conladed thatÂ  is a possibility thatÂ  SyariahÂ  PrinciplesÂ  areÂ  violatedÂ  byÂ  IslamicÂ  BankÂ  inÂ  termsÂ  ofÂ  itsÂ  capitalization.Â  ThisÂ  can beÂ  seeÂ  fromÂ  the missing of requirements that make it compulsory for all founders to make a statement letter which states that theÂ  financialÂ  capitalÂ  depositedÂ  toÂ  IslamicÂ  BankÂ  doesÂ  notÂ  comeÂ  fromÂ  aÂ  sourceÂ  whichÂ  isÂ  considered asÂ  haram accordingÂ  to SyariahÂ  Principle.Â  TheÂ  consequenceÂ  ofÂ  the missing requirementÂ  isÂ  theÂ  possibility ofÂ  receiving haramÂ  financialÂ  capitalÂ  from theÂ  founders.Â  ShouldÂ  this happen,Â  then Syariah PrincipleÂ  is violated.